2009
DOI: 10.1111/j.1468-2982.2008.01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention in Children With Migraine: A Controlled Comparative Study

Abstract: The aim of this study was to evaluate the visual attention of children with migraine and compare it with a control group. Thirty migrainous children and 30 controls without headache were subjected to a visual attention assessment with Trail Making Tests (TMT) A/B, Letter Cancellation Test, and the Brazilian computerized test Visual Attention Test, third edition. The migraine group was evaluated after 2 days without headache. The migraine group had an inferior performance compared with the control group on TMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 26 publications
5
41
0
Order By: Relevance
“…Our findings are supported by other pediatric and adult studies that showed cognitive deficits such as decreased processing speed, memory deficits, and attention problems [5][6][7][8][9][10][11] , as well as intelligence quotient (IQ) differences 14 . In an important, longitudinal study, Waldie et al 18 found impaired verbal skills in a migraine group when compared to a control group, more evident between 3-to-13-year-old migrainer children.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are supported by other pediatric and adult studies that showed cognitive deficits such as decreased processing speed, memory deficits, and attention problems [5][6][7][8][9][10][11] , as well as intelligence quotient (IQ) differences 14 . In an important, longitudinal study, Waldie et al 18 found impaired verbal skills in a migraine group when compared to a control group, more evident between 3-to-13-year-old migrainer children.…”
Section: Discussionsupporting
confidence: 89%
“…Riva et al 6 , reported worse visuomotor processing speed in both migraineur children with (n=17) and without (n=31) aura. Villa et al 7 , in a comparative and controlled study, found selective and alternate attention deficits in a migraine group. However, Haverkamp et al 8 did not find any cognitive disturbances in migraineurs when compared to their siblings without headache.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies concluded that there is a visual attention deficit in migraine patients (10,11). Since the prefrontal and cingulate cortices play a major role in attentional processing, we would expect that migraine patients have difficulties with correctly performing challenging saccadic eye movement tests which require adequate visual attention (12).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that patients with migraine [9][10][11] or tension-type headache [11] often display various attention problems.…”
Section: Introductionmentioning
confidence: 99%